Growth and nutrition of Urochloa brizantha cv. Marandu inoculated with plant growth promoting bacteria and under different doses of nitrogen (Research, Society and Development, 2020)
The demand for the production of adequate amounts of plant biomass is a major challenge for Brazilian livestock that faces a serious situation in relation to the degradation of most native or cultivated pastures, especially in soils deficient in biogenic nutrients such as nitrogen. The objective of the present study was to evaluate the growth and nutrition of Urochloa brizantha as a result of inoculation with Azospirillum brasilense associated with nitrogen fertilization. The experiment was conducted in a greenhouse at Universidade Paranaense - UNIPAR, Umuarama - PR. The experimental design was completely randomized, consisting of six treatments (control, inoculated without N, inoculated + 50 and 75 kg ha-1 N, without inoculation + 50 and 75 kg ha-1 N) and five replicates each. 10 days after sowing, excess plants were thinned leaving only five plants per pot. 60 days after sowing, the plants were collected for dry mass analysis, leaf elongation and leaf nutrient content. The inoculation resulted in a gain in the dry mass of the aerial part, length of the aerial part and number of tillers, however there was no gain in dry mass of the root. It was possible to observe a higher concentration of leaf nitrogen and chlorophyll index in treatments with higher concentrations of nitrogen fertilization, inoculated or not. Therefore, it is concluded that inoculation with A. brasilense associated with nitrogen fertilization proved to be an excellent ally in increasing production and in the development of U. brizantha cv. Marandu.